REFLECTIONS REGARDING THE ENFORCEMENT OF THE PREVENTION LAW IN THE AREA OF EMPLOYMENTS RELATIONSHIPS - Aurelian Gabriel ULUITU (Challenges of the Knowledge Society, 2018)
The Law no 270/2017 - Prevention Act is an inedited step in the Romanian legislation. For the first time in Romanian legislation, the ascertaining agent of a contravention has the obligation to establish several remedial measurements in order to clarify the legal framework of their specific activity. Because of the numerous contraventions regulated by the labor legislation, the Prevention Act concerns all the employers. Within the present paper, the author indicates the specific Labor law contraventions which permit the application of the Prevention Act and the contraventions which are incompatible with this Law. In the matter of contraventional liability, the relation between the public body responsible for control and enforcement, on the one hand, and the subject of law whose activity is to be checked in order to make sure that it complies with the law, on the other hand, involves a median element between the full compliance situation (abiding by the applicable legal provisions) and the non-compliance situation (not abiding by the rules is punishable by a civil fine). As in other areas covered by contraventional sanctioning, as far as employment relationships are concerned, the legislator elected a small number of contraventions to which the special rules provided for by the Prevention Law could be applied